Proceedings of Latin American and Caribbean Petroleum Engineering Conference 1999
DOI: 10.2523/53940-ms
|View full text |Cite
|
Sign up to set email alerts
|

Drilling in South America : A Wellbore Stability Approach for Complex Geologic Conditions

Abstract: TX 75083-3836, U.S.A., fax 01-972-952-9435. AbstractAn analysis approach is described which includes the effects of rock fabric strength anisotropy on wellbore instability. When drilling in geologically complex conditions -shown to be commonplace in the Andean foothills of South Americabedding-plane slippage, resulting from an unfavourable interaction between in-situ stresses, the well trajectory and bedding, is shown to cause severe instability for certain well trajectories. Case-history examples from the Ped… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 8 publications
0
2
0
Order By: Relevance
“…Vernik and Zoback (1990) analytically showed that there are four sectors around the wellbore that could satisfy the failure in the weak plane, which have been observed in the image log as two double-lobed BOs (Kowan et al, 2021). However, no double-lobed BOs have been observed in the current study since the BO morphology is highly controlled by the angle between the wellbore inclination and weak plane geometry (Okland & Cook, 1998;Willson et al, 1999). The angle between the normal of the weak plane and the wellbore axis is denoted as β n .…”
Section: Relations Between Metamorphic Texture Anisotropy and Breakoutsmentioning
confidence: 60%
“…Vernik and Zoback (1990) analytically showed that there are four sectors around the wellbore that could satisfy the failure in the weak plane, which have been observed in the image log as two double-lobed BOs (Kowan et al, 2021). However, no double-lobed BOs have been observed in the current study since the BO morphology is highly controlled by the angle between the wellbore inclination and weak plane geometry (Okland & Cook, 1998;Willson et al, 1999). The angle between the normal of the weak plane and the wellbore axis is denoted as β n .…”
Section: Relations Between Metamorphic Texture Anisotropy and Breakoutsmentioning
confidence: 60%
“…The stress state in the earth's crust controls stress concentration around a wellbore and therefore plays a critical role in wellbore instability, well stimulation operations, fluid flow in fractured reservoirs, and sand production (Bell 1996;Willson et al 1999). Knowledge of the stress state is not only important in the petroleum industry, but it is also vital in geotechnical applications and other solid earth sciences.…”
Section: Introductionmentioning
confidence: 99%